Application of a fuzzy algorithm for pH control in a struvite crystallisation reactor - Chanona, J (Water science and technology : a journal of the International Association on Water Pollution Research, 2006)
A struvite crystallisation process is highly dependent on pH. To achieve a high phosphorus recovery as struvite it is important to have an accurate control of pH in the reactor. The high non-linear response of pH value makes manual pH control difficult. Therefore, a software based on fuzzy logic control (FLC) has been developed to maintain the pH at a set value in a stirred reactor to crystallise struvite. The FLC developed has been based on Larsen's inference. In order to confirm the improvement of the pH stability using FLC software, different experiments have been carried out with manual control of the pH value, and with the FLC software. It has been demonstrated that using FLC software allows a precise control of pH with high stability, optimises the process, and minimises the operator intervention